Three-dimensional geoelectric model of the Golovanevsk suture zones of the Ukrainian Shield - B.I. Shyrkov; Т.К. Burakhovich; A.N. Kushnir (Геофизический журнал, 2017)
Thorough three-dimensional deep model has been plotted for the first time for the Golovanivsk suture zone of the Ukrainian shield and adjacent area applying Mtd3fwd R. L. Mackie's program based on geophysical experiment as MTS and MVP investigations. Anomalies of electro-conductivity in the Earth crust coinciding spatially with deep fault zones have been allocated. It has been confirmed that outside the limits of the GSZ heterogeneous earth crust and upper mantle are both observed. It has been shown that the areas of anomalously high resistance partially correspond to massifs of crystalline rocks (the Uman, the Korsun-Novomirgorod, the Novo-Ukrainian) in the Earth's crust and upper mantle.